Impact of Diabetic Mellitus on the Effect of Streptokinase in Acute Myocardial Infarction Patients (Medicine Today, 2013)
A prospective interventional study was carried out to compare  the thrombolytic effect of streptokinase between diabetic and  non-diabetic myocardial infarction patients. Out of 187 study  subjects with acute ST segment elevation myocardial  infarction (STEMI), admitted at coronary care unit, 126  patients were non-diabetic and 61 patients were diabetic.  Streptokinase was administered to all patients. Resolution  (reduction) of elevated ST segment was evaluated after 90 min  of streptokinase administration. Successful reperfusion  (=70% ST-resolution) was significantly higher in  non-diabetic than diabetic (p